2018
DOI: 10.1021/acs.macromol.8b00549
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetically Structured Lamellae Assembly in Periodic Banding of Poly(ethylene adipate) Crystals

Abstract: Nature tends to assemble hierarchical structures in similar ways to achieve compactness and functions. This work probes the interior lamellae assembly of crystalline spherulites of poly­(ethylene adipate) (PEA) with striking birefringence patterns versus some known biological structures for optical color diffraction. Three-dimensional dissecting onto interior lamellar structures of spherulites in poly­(ethylene adipate) (PEA) in bulk forms crystallized at 28 ± 3 °C were studied in correlation with thin-film fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Structured color reflection by photonic crystals in grating structures is common in nature. [ 40–44 ] Such grating architectures composed of cross‐hatch interior lamellae mutually with perpendicular intersections are also reported for ring‐banded PEA crystallized at T c = 28–30 °C known for displaying bio‐mimetic structures for iridescent properties, [ 39 ] which also resemble some of nature's crystal assemblies for bio‐photonic structures to produce complex light diffractions. [ 44–49 ] Such interior periodic assembly array in PBA ring‐banded spherulites is quite similar to those in beetles’ exoskeleton scales with a photonic crystal structure reported by Bartl, et.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Structured color reflection by photonic crystals in grating structures is common in nature. [ 40–44 ] Such grating architectures composed of cross‐hatch interior lamellae mutually with perpendicular intersections are also reported for ring‐banded PEA crystallized at T c = 28–30 °C known for displaying bio‐mimetic structures for iridescent properties, [ 39 ] which also resemble some of nature's crystal assemblies for bio‐photonic structures to produce complex light diffractions. [ 44–49 ] Such interior periodic assembly array in PBA ring‐banded spherulites is quite similar to those in beetles’ exoskeleton scales with a photonic crystal structure reported by Bartl, et.…”
Section: Resultsmentioning
confidence: 84%
“…Note that the actual topology profiles on the banded PBA's top surface might be inherently 2 times greater in depth than what is measured by AFM, because there are very narrow crevices (in the valley bands) not reachable by the AFM probe tip, which has been proven in a recent study. [ 38 ] Thus, the actual height profiles variations in the crystal assemblies might range between 200–300 nm, which falls in the half‐wavelengths of the visible light, [ 39 ] leading to potential photonic crystals with iridescence.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies [ 25–32 ] have shown that the hierarchical lamellar assembly mechanism is sensitive to the film thickness, blend composition, temperature, and crystallization with top cover. Furthermore, RBS dissection studies have revealed both radial and tangential assemblies of lamellae in banded spherulites.…”
Section: Introductionmentioning
confidence: 99%
“…Nature is the most skilled architect that can create complicated superstructures with fascinating biological functions including gene and enzyme complexes via hierarchically self-organized strategies. In the last decades, scientists have been trying to intimate the wonders of nature to build highly ordered architectures with rich functionalities, in which self-assembly of polymers is a powerful tool to construct superstructures by a bottom-up approach. For instance, three-dimensional (3D) helical hollow superstructures, supermicelles, and spheres-in-lamellae nanostructures have been fabricated by the hierarchical self-assembly of amphiphilic polymers and exploded in the applications of imaging, detection and microwave adsorption, and so forth. Despite commonly reported amorphous highly ordered structures, crystallized counterparts showed unique photoelectric properties. For example, a range of nanostructures with high crystallinity have been prepared by crystallization-driven self-assembly (CDSA). However, the building blocks for CDSA are still limited because only crystallizable or semi-crystallizable segments, such as polyferrocenyldimethylsilane, polycaprolactone, and poly­(lactic acid), and so forth, can be used as the core-forming block. ,,, …”
Section: Introductionmentioning
confidence: 99%